2021
DOI: 10.1002/path.5658
|View full text |Cite
|
Sign up to set email alerts
|

Renal deposition and clearance of recombinant poly‐IgA complexes in a model of IgA nephropathy

Abstract: IgA nephropathy (IgAN) is the most common type of glomerulonephritis worldwide, which follows a chronic but nonetheless highly variable course of progression. IgA immune complexes are the primary source of renal deposits in IgAN. Apart from the presence of granular IgA1 deposits in the glomerular mesangium and mesangial hypercellularity as common features, the detailed process of IgA1 deposition and clearance in the kidney remains unclear. We sought to examine the dynamics of IgA deposition and tissue plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…We used a passive induction model with 5 daily i.v. injections of purified recombinant rat rIgA in rats ( 17 ) ( Figure 6A , left). Rats developed prominent IgA deposition in the glomerulus ( Figure 6B , top).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a passive induction model with 5 daily i.v. injections of purified recombinant rat rIgA in rats ( 17 ) ( Figure 6A , left). Rats developed prominent IgA deposition in the glomerulus ( Figure 6B , top).…”
Section: Resultsmentioning
confidence: 99%
“…Human IgA1-Fc CH2-CH3-TP cDNA and its mutant for C471S were fused to sequences encoding IL-2 signal peptide and 6×His-tag at the 5′-end in pcDNA3 vector (Invitrogen). Methods for protein expression and purification were described previously ( 17 ). Briefly, rat IgA analogs were expressed in the BL21 DE3 strain of E .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the receptors cleaning the mesangium can be saturated if the IgA deposition rate is high. This hypothesis has recently been mentioned [61].…”
Section: β4galt-i Ko Modelmentioning
confidence: 86%
“…IgA nephropathy has been an important cause of end-stage renal disease among young adults. The predominant histological characteristics are immune deposits dominated by granular diffuse IgA (primarily comprising polymeric IgA1) in the mesangial region, usually linked to increased mesangial cells along with matrix expansion ( Xie et al, 2021 ). In China, IgA nephropathy occupies 45.26% of primary glomerular diseases, and remains the most common cause of uremia (26.69%) ( Li Y. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%